Click here : (to find out how I survived seventh grade) : a novel - Vega, Denise (New York : Little, Brown, 2006)
Seventh-grader Erin Swift writes about her friends and classmates in her private blog, but when it accidentally gets posted on the school Intranet site, she learns some important lessons about friendship.
4.4
3-6
3-6
Wilson's Junior High School
School Library Journal
Publisher's Weekly
Keywords: Friendship -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Blogs -- Juvenile fiction; Computers -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Fiction; Interpersonal relations -- Fiction; Blogs -- Fiction; Computers -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Friendship -- Fiction; Interpersonal relations -- Fiction; Blogs -- Fiction; Computers -- Fiction; Middle schools -- Fiction; School stories